Better migrants, better PISA results: Findings from a natural experiment - Maria A. Cattaneo; Stefan C. Wolter (IZA Journal of Migration, 2015)
Switzerland changed its migration policy in the 1990s from a "non-qualified only" policy to one of almost free movement of labor. To analyze the impact of this policy change on the schooling outcomes of children of first-generation migrants, the paper compares the PISA results of first-generation pupils in 2000 with the scores of children tested in 2009, whose parents immigrated after the policy changed. We find that around 75% of the 40-point increase in the PISA score of first-generation immigrant students was due to changes in the individual background characteristics of their parents and to improved school composition.
Keywords: I21; I24; J15; 330; Migration; PISA; Blinder-Oaxaca decomposition; Natural experiment